Pengaruh Insentif dan Beban Kerja terhadap Kinerja Karyawan di PT Makmur Alam Seiwampu Binjai - Ramadhini, Rizky; Julkarnain, Julkarnain; Syafrizal, Syafrizal (JRMB (Jurnal Riset Manajemen & Bisnis), 2023)
The formulation of the problem in this study is how the influence of the work incentives on employee performance. How does workload affect employee performance. How the incentives and workload affect employee performance. The purpose of this study is to determine and analyze the influence of the work incentives on employee performance. To know and analyze the effect of workload on employee performance. To know and analyze the influence of the incentives and workload on employee performance. The sample in this study amounted to 40 employees. Data analysis techniques in this study used descriptive analysis and multiple linear regression analysis. The results of this study explain the incentives variables have a positive and significant effect on employee performance. Workload variables have a positive and significant effect on employee performance. Incentives and workload have a positive and significant effect on employee performance.